Assessment of Economic Losses Caused by the Mangrove Degradation: Case study-Fishing community in Puttalam Lagoon - Ruzaik, Fareena; Niyas, A. Rose (The Research Publication, 2020)
Puttalam Lagoon has a rich mangrove ecosystem. The exploitation of such heritage for various reasons has become a threat to the fishing community in terms of economic yield. During 1977-2018, 68-72% of the mangrove species have been depleted, which was negatively impacted to fish productions. Hence, this study focuses to assess the economic fatalities, face by the fishing community. The field study has been carried out to collect primary data, by way of a questionnaire, direct observation, and constructive discussion; following the stratified sampling method. The 91 questionnaires from the six (06) fisheries inspector division, around the lagoon, were filled; which is 1% of the total active fishing population. The secondary data has also been used. The analysis revealed that 64% of people are frequently affected by flooding and 68% by cyclones. Approx. 91% of the Fishermen had an opinion that the seafood production and subsequent income of them have drastically declined, due to the depletion of the mangrove ecosystem. Before the degradation of mangroves, over 80% of Fishermen earned their better income and had remarkable savings for their future needs. Over 80% of fishermen had a good income, but over 90% had low satisfaction level concerning their monthly average expenses, due to the increasing trend of the price for fishing instruments/consumables and cost of living. This shows that depletion of mangroves has a linear relationship with fish production and income. Therefore, the coastal ecosystem of Puttalam Lagoon should be managed, participating relevant stakeholders, implementing existing laws, declaring Puttalam Lagoon as a mangrove protection zone, and promoting secondary income earning source (eco-tourism) to facilitate dwellers to meet future contingency requirements
Keywords: Mangroves, fishing community, lagoon, degradation and re-plantation